2017
DOI: 10.3390/v9110313
|View full text |Cite
|
Sign up to set email alerts
|

Protoparvovirus Cell Entry

Abstract: The Protoparvovirus (PtPV) genus of the Parvoviridae family of viruses includes important animal pathogens and reference molecular models for the entire family. Some virus members of the PtPV genus have arisen as promising tools to treat tumoral processes, as they exhibit marked oncotropism and oncolytic activities while being nonpathogenic for humans. The PtPVs invade and replicate within the nucleus making extensive use of the transport, transcription and replication machineries of the host cells. In order t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 131 publications
(199 reference statements)
1
29
0
Order By: Relevance
“…Previous research has reported that other PtPVs use clathrin-mediated endocytosis to gain access to cells and progress the infection (reviewed in Reference [ 3 ]). Our results are therefore in agreement with the idea that clathrin-mediated endocytosis is the default entry pathway for PtPVs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous research has reported that other PtPVs use clathrin-mediated endocytosis to gain access to cells and progress the infection (reviewed in Reference [ 3 ]). Our results are therefore in agreement with the idea that clathrin-mediated endocytosis is the default entry pathway for PtPVs.…”
Section: Discussionmentioning
confidence: 99%
“…The rodent H-1 protoparvovirus (H-1PV) belongs to the Parvoviridae family, genus Protoparvovirus [ 1 ]. This genus also includes Rodent protoparvovirus 1 (H-1PV, Kilham rat virus, LuIII virus, minute virus of mice (MVM), mouse parvovirus, tumour virus X, rat minute virus), Rodent protoparvovirus 2 (rat parvovirus 1), Carnivore protoparvovirus 1 (canine parvovirus (CPV) and feline panleukopenia parvovirus (FPV)), Primate protoparvovirus 1 (bufavirus) and Ungulate parvovirus 1 (porcine parvovirus (PPV)) [ 2 , 3 ]. Protoparvoviruses (PtPVs) are single-stranded DNA viruses with an icosahedral capsid of about 25 nm diameter.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[45][46][47][48][49][50] A particularly suited model for these studies is the icosahedral capsid of the minute virus of mice (MVM). 51,52 The MVM capsid ( Fig. 1A and B), one of the smallest (25 nm in diameter) and structurally simplest viral NPs known, is made of a minimum number (60) of structurally equivalent protein monomers that have the same sequence and fold.…”
Section: Introductionmentioning
confidence: 99%